2005
DOI: 10.1093/aob/mci214
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Oxygen Dynamics in the Freshwater Isoetid Lobelia dortmanna and the Marine Seagrass Zostera marina

Abstract: The build-up of O2 in the pore-water of L. dortmanna sediments during the day as a result of high release of photosynthetic O2 from roots and low O2 consumption of sediments means that sediment, aerenchyma and water are important O2 sources for respiration during the following night, while Z. marina relies on the water column as the sole source of O2 because its sediments are anoxic. These differences between L. dortmanna and Z. marina appear to represent a general difference between the isoetid species mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(101 citation statements)
references
References 50 publications
4
95
2
Order By: Relevance
“…At night, seagrasses translocate O 2 from the water column to the sediments through their leaf tissues to support root and rhizome R and also release O 2 into the sediments , Sand-Jensen et al 2005. Binzer et al (2005) found a logarithmic increase in the partial pressure of O 2 in seagrass tissue with flow that they attributed to increasing passive O 2 uptake from reduction in the diffusive boundary layer.…”
Section: Long Timescales: Monthly To Seasonalmentioning
confidence: 99%
“…At night, seagrasses translocate O 2 from the water column to the sediments through their leaf tissues to support root and rhizome R and also release O 2 into the sediments , Sand-Jensen et al 2005. Binzer et al (2005) found a logarithmic increase in the partial pressure of O 2 in seagrass tissue with flow that they attributed to increasing passive O 2 uptake from reduction in the diffusive boundary layer.…”
Section: Long Timescales: Monthly To Seasonalmentioning
confidence: 99%
“…By this system, oxygen is transported to the underground parts of the plants (Sand Jensen et al 2005). Part of the oxygen transported downwards is released in the root zone, where it sustains a number of beneficial oxidation processes (Laanbroek 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The direct comparison of d 34 S values with other isoetids is constrained by the lack of studies of H 2 S intrusion in isoetids as the phenomenon has received little attention due to naturally low SO 4 2-concentrations in oligotrophic softwater lakes (Holmer et al 1998). In addition, isoetids loose most of the O 2 produced in the photosynthesis via ROL so that the rhizosphere is often completely oxidized (Pedersen et al 1995;Sand-Jensen et al 2005b) and so, sulfate reduction is of little quantitative importance in isoetid populations. In seagrasses, however, H 2 S intrusion has been extensively investigated and here, sulfate reduction is important due to naturally higher levels of SO 4 2- (Holmer et al 2003) and much lower rates of ROL from seagrasses (Jensen et al 2005;Sand-Jensen et al 2005b;Møller and Sand-Jensen 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, isoetids loose most of the O 2 produced in the photosynthesis via ROL so that the rhizosphere is often completely oxidized (Pedersen et al 1995;Sand-Jensen et al 2005b) and so, sulfate reduction is of little quantitative importance in isoetid populations. In seagrasses, however, H 2 S intrusion has been extensively investigated and here, sulfate reduction is important due to naturally higher levels of SO 4 2- (Holmer et al 2003) and much lower rates of ROL from seagrasses (Jensen et al 2005;Sand-Jensen et al 2005b;Møller and Sand-Jensen 2008). d 34 S varies among species (Frederiksen et al 2008), but d 34 S values for L. dortmanna fall within the lower range of those observed for seagrasses (Zostera marina, Posidonea oceanica; Holmer and Nielsen 2007;Frederiksen et al 2008, or Cymodocea serrulata;Povidisa et al 2009), although they are exposed to H 2 S levels more than 100-fold higher than L. dortmanna in the present study.…”
Section: Discussionmentioning
confidence: 99%